The effect of health education on ability to perform a breast examination self-consciousness for students of the pediatric health product product faculty of teacher training and education megarezky university - Juwita, Juwita; Asli, Kartika; Amin, Susanti (Innovative Approaches in Health Science Journal, 2024)
Background: Based on data from the Physical Education Study Program, Faculty of Teacher Training and Education, Megarezky University, there are still many female students who don't know how to do SADARI, don't know what SADARI is. This research aims to identify the ability of students from the Physical Education Study Program, Faculty of Teacher Training and Education, Megarezky University, to perform SADARI and the influence of Health Education on the ability to perform SADARI among students from the Physical Education Study Program. Method: This type of research is quantitative research with a research design using quasi-experimental (Quasi-Experimental). This research uses the pretest-posttest design method. The target population in this study was students of the Physical Education Study Program and the ability of students after being given health education was found to have 12 respondents (75.0%) who were unable, and 4 respondents who were unable (25.0%). Results: Wilcoxon test results with a p-value of 0.019, which means p < α (0.05), which means Ho is rejected and Ha is accepted. Thus, there is an influence of health education on the SADARI examination as an early detection of breast cancer on the ability of physical education study program students at FKIP Megarezky University. Conclusion: It is hoped that health workers, especially midwives, will provide more optimal information and knowledge about contraception, especially regarding counseling on contraceptive choices